ЕСТЕТИЧНА СУТНІСТЬ ТА СПЕЦИФІКА КОРЕКЦІЙНО-ПЕДАГОГІЧНОЇ ПРАЦІ ДЕФЕКТОЛОГА - Демченко І. І.; Білан В. А.; Бабій І. В.; Черніченко Л. А. (World Science, 2019)
In the article the problem of increase of efficiency of professional preparation of a special education teacher is analysed, the meaning of the concept “Correction-pedagogical work” is defined, the essence of work of a special education teacher is grounded, the functions of its aesthetic and therapeutic competence are exposed, and also the aesthetic aspect of correction-pedagogical technology of communication of a special education teacher with children with special educational needs.